Cryopreservation of Equine and Bovine Erythrocytes Using Combined Protective Media - Ulizko, Pavlo Yu.; Bobrova, Olena M; Nardid, Oleg A; Zubov, Pavlo М.; Kovalenko, Igor F.; Kuchkov, Vadim M.; Vodopyanova, Larisa A. (Problems of Cryobiology and Cryomedicine, 2019)
A comparative analysis of the effectiveness of equine and bovine erythrocytes’ cryopreservation with the use of one component (20% DMSO) and combined (10% DMSO, 20% PEO-1500) protective medium was carried out. Using fluorescence microscopy and flow cytometry, it has been shown that the 3-DAB fluorescent dye paints the membranes of red blood cells and can be used to evaluate their condition at all cryopreservation stages. It was found that the use of combined protective medium can significantly improve the results of cryopreservation of equine and bovine red blood cells in comparison with one-component media. By cytometric data it has been defined that the parameters of equine erythrocytes after preservation in DMSO-based medium did not correspond the control even after cryoprotectant washing, but after freezing in combined cryoprotective medium and cryoprotectant washing they matched the control. The fluorescence intensification of equine and bovine erythrocytes on fluorescence images and changes in cytograms after mixing cells with 20% DMSO suggests its strong membranotropic influence. Hemolysis level with applying a combined cryoprotective medium of equine and bovine erythrocytes is significantly lower than with the application of 20% DMSO after all cryopreservation stages. Probl Cryobiol Cryomed 2019; 29(3): 255–265.